Vitamin K2 deficiency associated with short stature in children: a cross-sectional study - Yanjie Shen; Geyong Shi; Shumei Wen; Wei Luo; Ke Wang (BMC Pediatrics)
Abstract Background Short stature in children is a common concern that can result from various underlying conditions. While factors such as growth hormone deficiency and nutritional deficiencies are well-known contributors, the role of vitamin K2 (VK2) in the development of short stature remains underexplored. This study aimed to investigate the association between VK2 status and short stature in children. Methods A total of 730 children aged 3–16 years were enrolled and divided into three groups: short stature group (n = 191), near-short stature group (n = 357), and normal stature group (n = 182). Clinical characteristics and growth-related indicators including serum VK2 levels, bone mineral density (BMD), insulin-like growth factor 1 (IGF-1), and 25-hydroxyvitamin D (25-(OH)D) were collected. VK2 was analyzed both as a categorical variable (VK2 deficiency vs. normal status) and as a continuous variable, logistic regression models were applied to assess the association between VK2 status and short stature using both approaches. Correlations between VK2 status and other growth-related indicators were also examined. Results The prevalence of VK2 deficiency was higher in children with short stature (80.6%) and near-short stature (64.7%) compared to those with normal stature (32.4%) (P < 0.05). Multiple logistic regression models showed that higher serum VK2 levels were significantly associated with a decreased risk of short stature (aOR = 0.005, 95% CI: 0.001–0.036) and near-short stature (aOR = 0.023, 95% CI: 0.006–0.085); and VK2 deficiency was significantly associated with increased risk of short stature (aOR = 5.934, 95% CI: 3.372–10.443) and near-short stature (aOR = 3.233, 95% CI: 2.095–4.989) after adjusting for covariates. Additionally, serum VK2 levels were positively correlated with IGF-1-SDS and 25(OH)D (P < 0.05). Conclusions VK2 deficiency was significantly associated with an increased risk of short stature in children. Further longitudinal studies are warranted to elucidate the causal relationship between VK2 deficiency and growth disorders in pediatric populations.